Pengaruh Model Problem Based Learning Berbantuan Zoom Meeting Terhadap Hasil Belajar Siswa - Irfandi Idris; Arief Hasjaya; Sulkipli M.; Andi Maryam; Rizky Ekawaty Ahmad (Program Studi PGSD Universitas Madako Tolitoli, 2022)
Learning outcomes are the ability to acquire thoughts from the knowledge obtained. Brave or remote learning systems make students increasingly constrained by access to knowledge so one way is to change the pattern of learning models. Problem-based learning or problem-based learning is a learning model that wants to be applied at this time to improve student learning outcomes on goods and services, so a zoom meeting application is also needed to help students regain their knowledge as virtual media. This quantitative research uses a quasi-experimental research method using a non-equivalent design. This research was conducted at Muhammadiyah Elementary School, Sorong City. The population in this study was class IV as many as 60 students. A sample of 30 students in class IVA and 30 class IVB. Data collection techniques using learning achievement tests, observation and documentation. Data analysis used independent sample t test (t test) with a significant level of 0.05 assisted by SPSS 25. The result was an increase in the average value of the class given treatment with the PBL (Problem Based Learning) learning model assisted by zoom meeting on learning outcomes.